The Relationship Between Polyvictimization, Emotion Dysregulation, and Social Support Among Emerging Adults Victimized During Childhood. Issue 5 (27th May 2016) - Barnes, Sarah E.; Howell, Kathryn H.; Miller-Graff, Laura E.
ABSTRACT: The purpose of this study was to examine the relationship between childhood polyvictimization and social support from family and friends in emerging adulthood. Emotion dysregulation was also investigated as a potential mediator underlying this relationship. Results indicated that childhood polyvictimization was significantly related to lower reports of social support from both family and friends. Emotion dysregulation was positively related to childhood polyvictimization, and negatively related to social support from family only. Additionally, emotion dysregulation partially mediated the relationship between childhood polyvictimization and support from family, suggesting that the ability to regulate one's emotions could be particularly influential in family relationships. Results underscore the pervasive nature of childhood polyvictimization, and offer directions for intervention efforts targeted at emerging adults with polyvictimization histories.